Pengkajian Islam Di Era Digital: Pendekatan Teknologi dan Media - Nuranisa A. Isima; Abdullah .; Muh Arif (CV. ITTC INDONESIA, 2026)
This research examines the influence of digital technology in the study of Islam in the modern era. The background of this research shows that the rapid development of information technology has changed the way people understand, disseminate and practice Islamic teachings. This research aims to explore the role of digital technology and media, the challenges faced, and the optimal approach in utilizing them for Islamic studies. The method used is descriptive qualitative with a literature study approach that includes analyzing scholarly sources, online publications, and the works of scholars. The data shows that digital technology facilitates access to Islamic sources, such as the Qur'an, hadith, and tafsir, through platforms such as mobile applications, social media, and digital libraries. However, the digital era also presents challenges such as misinformation, radicalism and digital divide. In addition, the quality of content and digital literacy of the community are the main obstacles in ensuring the authenticity of the information spread. The conclusion of this study emphasizes the importance of digital and Islamic literacy to filter correct information, the development of credible digital platforms, and the production of quality content that is easy to understand. This research recommends collaboration between scholars, Islamic institutions, and technology developers to optimize the use of digital media in Islamic studies, so as to make a positive contribution to da'wah.